2019
DOI: 10.1016/j.ejmech.2019.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Organoseleno cytostatic derivatives: Autophagic cell death with AMPK and JNK activation

Abstract: Selenocyanates and diselenides are potential antitumor agents. Here we report two series of selenium derivatives related to selenocyanates and diselenides containing carboxylic, amide and imide moieties. These compounds were screened for their potency and selectivity against seven tumor cell lines and two non-malignant cell lines.Results showed that MCF-7 cells were especially sensitive to the treatment, with seven compounds presenting GI 50 values below 10 µM. Notably, the carboxylic selenocyanate 8b and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, the autophagic flux, SQSTM1/p62, was downregulated confirming the autophagy process. Phosphorylation of AMPK and JNK was also studied because they have shown to be implicated in autophagy-mediated cell death [27]. As expected, both compounds induced JNK and AMPK phosphorylation.…”
Section: Apoptosis and Cell Cycle Arrestmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, the autophagic flux, SQSTM1/p62, was downregulated confirming the autophagy process. Phosphorylation of AMPK and JNK was also studied because they have shown to be implicated in autophagy-mediated cell death [27]. As expected, both compounds induced JNK and AMPK phosphorylation.…”
Section: Apoptosis and Cell Cycle Arrestmentioning
confidence: 64%
“…Accumulating evidence in the literature has illustrated that among the different selenated scaffolds, selenenocyanate [19,20] and diselenide [21][22][23] fragments are important pharmacophores that significantly suppress breast cancer. Furthermore, our research group has reported that selenocyanate and diselenide entities possess potent antitumor activity [24][25][26][27]. Consequently, these motifs are considered as an encouraging template for designing a new category of selenium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the organoseleno derivatives (Figure , compounds 1 and 2 ) have been reported to trigger ADCD in human breast carcinoma MCF-7 cells by activating AMPK and JNK pathway, as well as increasing beclin-1 and LC3II and reducing p62 levels . Moreover, compound 1 and compound 2 induced cell death could be repressed by autophagy inhibitors (wortmannin and chloroquine) but could not be affected by the caspase inhibitor (Z-VAD-FMK) . It is suggested that ADCD is the way by which compound 1 and compound 2 may cause their effects .…”
Section: Autophagy-dependent Cell Death and Relevant Small Molecules ...mentioning
confidence: 99%
“…Moreover, compound 1 and compound 2 induced cell death could be repressed by autophagy inhibitors (wortmannin and chloroquine) but could not be affected by the caspase inhibitor (Z-VAD-FMK) . It is suggested that ADCD is the way by which compound 1 and compound 2 may cause their effects . Fluorinated thiazolidionol (Figure , compound 3 ) can induce AMPK activation and inhibit PI3K/AKT/mTORC1 and MEK/ERK pathways, triggering ADCD in pancreatic ductal adenocarcinoma MIA PaCa-2 and PANC-1 cells proved by increased cytoplasmic vacuoles formation and enhanced autophagic flux .…”
Section: Autophagy-dependent Cell Death and Relevant Small Molecules ...mentioning
confidence: 99%
See 1 more Smart Citation